Infant crossed renal ectopia with UPJ obstruction repaired via robot-assisted laparoscopic pyeloplasty. Issue 1 (February 2018) - Puttmann, K.; Huang, G.O.; White, J.T.; Kukreja, K.; Seth, A.; Koh, C.J.
Summary: Introduction: We present a robot-assisted approach to surgical treatment of UPJ obstruction associated with crossed renal ectopia in a male infant. Methods: A 31 year-old woman presented at 37 weeks gestation for prenatal hydronephrosis and delivered at 39 weeks. Renal ultrasound identified the bladder and right kidney in a crossed ectopic position in the left pelvis, and MRI showed the cystic lesion to be hydronephrosis associated with a ureteropelvic junction obstruction of the crossed ectopic right kidney. At three months of age, a robot-assisted laparoscopic dismembered pyeloplasty was performed. Post-operative renal ultrasounds at one, two, and 7 months showed persistent but decreasing hydronephrosis. He remains asymptomatic. Discussion: Crossed renal ectopia with associated ureteropelvic junction obstruction has been reported in the literature and managed using both open and minimally invasive approaches. To our knowledge, this is the first reported robot-assisted pyeloplasty performed for this condition in an infant. Conclusions: With careful patient selection, the robot-assisted laparoscopic approach can be applied to infants that require pyeloplasty for kidneys with anomalous development that have evidence of ureteropelvic junction obstruction.